Social cooperatives: whether the European experience takes root in Ukraine? - Lyakh, O. (Економічний вісник Донбасу, 2016)
The potential contribution of social cooperatives and other form of social enterprises to work integration, job creation, and service delivery remains largely unrealized in Ukraine. This paper focuses on an analysis of the role of social cooperation in providing employment opportunities and wide range of general interest services for stakeholders and local communities. Institutional aspects and legal frameworks are considered in order to define the appropriate environment system for social enterprises sector support and fostering. Attention was also paid to frame of the policy for social cooperatives support on the mezzo-level (regional), taking in account ongoing decentralization of public authority that is allowing to clarify what level of authority should be responsible for concrete policy measures elaborating. Потенційний внесок соціальних кооперативів та інших форм соціальних підприємств в інтеграцію, зайнятість, створення робочих місць і надання послуг залишається значною мірою нереалізованим в Україні. Дана стаття присвячена аналізу ролі соціальної кооперації в забезпеченні можливостей для зайнятості і широкого спектру соціальних послуг для спільнот за інтересами та місцевих громад. Інституційні аспекти та правові рамки, розглядаються з метою визначення відповідної системи інфраструктури і середовища для підтримки і стимулювання сектору соціальних підприємств. Увагу також приділено рамкам політики для підтримки соціальних кооперативів на мезорівні (регіональному), беручи до уваги триваючу децентралізацію публічної влади, яка, що дозволяє уточнити: який рівень влади повинен нести відповідальність за конкретні заходи політики розвитку. Потенциальный вклад социальных кооперативов и других форм социальных предприятий в интеграцию, занятость, создание рабочих мест и оказание услуг остается в значительной степени нереализованным в Украине. Данная статья посвящена анализу роли социальной кооперации в обеспечении возможностей для занятости и широкого спектра социальных услуг для групп по интересам и местных общин. Институциональные аспекты и правовые рамки, рассматриваются с целью определения соответствующей системы инфраструктуры и среды для поддержки и стимулирования сектора социальных предприятий. Внимание также уделено рамкам политики для поддержки социальных кооперативов на мезоуровне (региональном), принимая во внимание продолжающуюся децентрализацию публичной власти, что позволяет уточнить: какой уровень власти должен нести ответственность за конкретные меры политики развития.